Analysis of P53, P16INK4A, PRB and cyclin D1 expression and human papillomavirus in primary ovarian serous carcinoma - Bilyk, O.O.; Pande, N.T.; Buchynska, L.G. (Experimental Oncology, 2011)
Aim: To evaluate the prognostic relevance of key cell cycle regulatory proteins p53, p16INK4a, pRb and Cyclin D1 expression, the presence of high risk HPVs and their association with clinicopathological parameters and the clinical follow up in ovarian cancer patients. Methods: 53 cases of primary ovarian serous carcinomas were immunohistochemically examined for the expression of p53, p16INK4a, pRb and Cyclin D1 proteins. Tumor DNA was extracted from paraffin blocks and subjected to HPV 16 and 18 testing. The association between HPV 16 and 18 E6 oncoprotein and cell cycle proteins expression in ovarian carcinomas also was evaluated by immunohistochemistry. Results: We demonstrated that a majority of moderately and poorly differentiated ovarian carcinomas are characterized by strong expression of p53 and p16INK4a proteins. In contrast, strong staining with cyclin D1 antibody was observed in well differentiated tumors. The correlation between strong p53, pRb, Cyclin D1 and clinical stages of disease was also observed. We show that patients with high positivity for p53, p16INK4a and Cyclin D1 had a poor prognosis and reduced overall survival. The presence of HPV 16/18 DNA was detected in 17% of ovarian carcinomas. The tumor tissues that reacted positively to HPV E6 antibody in focal and diffuse manners had also significantly low p53 expression profile. Conclusion: These findings suggest that p53, p16INK4a and Cyclin D1 expression and HPV infection may represent a promising tool toward the identification of ovarian cancer patients with poorer prognosis and shorter survival who might therefore need a more aggressive therapy and HPV screening.